Doping-dependent fixed charges in SiC/SiO2 structure - Kyota Mikami; Mitsuaki Kaneko; Tsunenobu Kimoto (Applied Physics Express)
Doping-dependent fixed charges were found in SiC/SiO _2 structures through a study on threshold voltage in both n- and p-channel SiC metal-oxide-semiconductor field-effect transistors (MOSFETs) with various body doping concentrations. Positive fixed charges increase for the p-body (n-channel) devices and negative fixed charges increase for the n-body (p-channel) devices, both of which retard the increase of threshold voltage in MOSFETs with increasing the body doping.